Silent cerebral infarction in chronic heart failure: Ischemic and nonischemic dilated cardiomyopathy - Kozdag, Guliz (Dove Medical Press, 2008)
OBJECTIVES: Patients with dilated cardiomyopathy (DCM) may have a high incidence of clinically asymptomatic silent cerebral infarction (SCI). Prevalence of SCI and its risk factors may differ between ischemic and nonischemic DCM. The purpose of this study was to evaluate prevalence and related parameters of silent cerebral infarction in patients with ischemic and nonischemic DCM. METHODS: Patients with ischemic and nonischemic DCM (53 male, 19 female, aged 62 ± 12 years) were included in the study. Etiology of DCM was ischemic in 46 and nonischemic in 26 patients. Fifty-six age- and gender-matched healthy volunteers served as a control group for comparison of SCI prevalence. RESULTS: Prevalence of SCI was 39%, 27%, and 3.6% in ischemic, nonischemic DCM, and control group, respectively (ischemic DCM vs control group, p < 0.001, nonischemic DCM vs control group, p = 002). In patients with nonischemic DCM, the mean age of the subjects with SCI was significantly higher than that of subjects without lesions (67 ± 5 years vs 53 ± 13, p < 0.001), whereas in ischemic DCM NHYA Functional Class was statistically higher in patients with SCI than without SCI (p = 0.03). In both groups, patients with SCI had lower systolic functions than patients with normal MRI findings. In multivariable logistic regression analysis, restrictive type of diastolic filling pattern was found as an independent factor for SCI occurrence on the whole patient population (OR: 16.5, 95% CI: 4.4–61.8, p < 0.001). CONCLUSION: SCI is common in patients with both ischemic and nonischemic DCM. In univariate analysis, both groups have similar systolic and diastolic characteristics in the occurrence of SCI. Logistic regression analysis revealed that restrictive diastolic filling pattern is an independent risk factor in the occurrence of SCI for the whole patient population.